Exploration of Simulacra in Moderation Messages: Analysis of Salafi Dakwah on Youtube - Abdul Rahman Matondang; Hasan Sazali; Zainun Zainun (Journal La Sociale, 2024)
This research aims to deepen the moderation messages expressed by Ustad Salafi on the YouTube platform, as well as analyze how the reality of religious moderation is constructed through the perspective of Jean Baudrillard's simulacra theory. The research method applied involved content analysis of videos uploaded by Ustad Salafi, as well as interviews with viewers and followers. The use of Nvivo software makes it easier to code and analyze the collected data. The findings of this research indicate that Ustad Salafi seeks to promote messages of tolerance and peace, by mixing religious principles with the local cultural context. The messages of moderation conveyed through this digital platform have a significant impact in shaping religious discourse and supporting a more inclusive understanding of Islam, especially in the context of Indonesia's multicultural society. This research also highlights the complex dynamics between Ustad Salafi's online persona and the moderation messages he conveys. This shows the importance of understanding how digital media influences people's perceptions of religion and culture, as well as the complexity in the process of forming opinions and beliefs. Thus, this research makes a valuable contribution in understanding the role of digital media in influencing contemporary society's thinking and behavior regarding religious moderation.